Ferric hydroacid & diamine complex as draw solute for forward osmosis (FO) desalination processes - Manal Mounir (Elsevier, 2021)
Forward osmosis (FO) is being one of the recent technologies widely studied for desalination. FO mainly uses osmotic pressure gradient unlike reverse osmosis (RO) that uses hydraulic pressure gradient. So increasing the osmotic pressure is highly influencing the water flux in FO systems. A new type of draw solute used for enhancing the FO process is mixed ligand PDA-Fe-CA complex (Ferric hydroacid & diamine). Mixed ligand PDA-Fe-CA complex is a complex from iron–citric complex (Fe-CA) functionalized by 1,2phenylenediamine ligand. The resulting complex suggested structure was investigated by FTIR, elemental analysis, and spectrophotometric analysis proving the successful coordination of 1,2phenylenediamine to Fe, besides the successful coordinating of citric acid to Fe. The molar ratio for this complex was found to be 1:1:2 of Fe: CA: PDA. The performance of the produced complex was investigated using commercial FO membranes in batch FO system. 40 g/L (0.06 M) of PDA-Fe-CA produces water flux of 21.5 LMH when tested with distilled water as feed solution, and water flux values of 18, 15.8, 14, and 12.3 L/m2hr were gained when saline water were used as feed solution with concentrations of 3,000, 7,000, and 12,000 mg/L respectively. And the water flux was 7.9 LMH when synthetic sea water (35,000 mg/L NaCl) was used as feed solution.